TUGAS DAN WEWENANG OMBUDSMAN REPUBLIK INDONESIA DALAM PELAYANAN PUBLIK MENURUT UU NO. 37 TAHUN 2008 - Setiadjeng Kadarsih (Jurnal Dinamika Hukum, 2010)
Ombudsman RI is an institute that has an autonomy and it doesn’t have organic relationship with other state and governance institutes and also it runs its duties and rights free from the involvement of other authority. This institute has right to control the establishment of public service. Ombudsman’s right detail exists in Article 8 Law Number 37Year 2008 concerning ombudsman RI. Besides, OMBUDSMAN is allowed to give advice to the government to make reparation and perfection of organization and procedures of public service in order to avoid administration problem.Keywords: duty, right, public service